MAKSIMILISASI PENGGUNAAAN APLIKASI DIGITAL UNTUK MENUNJANG KINERJA ADMINISTRASI PERANGKAT DESA DI KECAMATAN BAJENG KABUPATEN GOWA - Oktavianty; Alamsyah Agit (ICON Publisher, 2026)
Bone Village is one of the smallest administrative areas located in Bajeng District, Gowa Regency. As an effort to support the administrative performance of village officials, which still requires attention, the use of digital applications is needed so that administrative activities can be managed in a more structured and systematic manner. One of the digital applications used is Microsoft Excel. Microsoft Excel is a spreadsheet application program designed to process and calculate numerical data (numbers). The development and implementation of digital applications in the village administrative system in Bone Village are expected to improve public services so that they become more efficient, precise, and accurate. Based on the results of a survey conducted to support the sustainability of administrative performance development, a community service activity was organized to improve and facilitate local residents in managing administrative matters. The activity was carried out through three stages: a material presentation session, a question-and-answer session, and a discussion session. The evaluation results of this activity showed the enthusiasm of community leaders in Bajeng District, Gowa Regency, to immediately implement the use of digital applications. As an initial step, they will apply this technology for their own administrative activities; however, further assistance and collaboration with various parties are still needed so that it can provide greater benefits for the village. This activity also serves as a consideration for the government to intensify efforts in encouraging the use of digital application systems for the wider community.